Peripheral extremity surgery performed during the Syrian conflict - A scoping review. - Anas Khan; Usman Ammar; Aula Abbara; Mahmoud Hariri; Ammar Darwish; Jude Alawa (PLOS Global Public Health)
The protracted Syrian conflict has devastated healthcare infrastructure across Syria with impacts on both the conflict and non-conflict related surgical needs of patients. This review summarises the literature related to peripheral limb surgery performed in Syria between March 2011 to January 2024 to determine the influence of the conflict on surgical capacity and provision. A systematic review based on Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR) guidelines was performed using six academic and one grey literature database. Studies that included clinical-epidemiological descriptions of procedures in orthopaedic, vascular and plastic surgery were included for quantitative and narrative analysis. The search resulted in 3951 papers, of which 7 met inclusion criteria. Studies varied widely in sample size (range: 25-3835; total: 7749), design, and outcomes. Procedures spanned orthopaedic (1285, 31%), vascular (741, 18%), and plastic surgery (2145, 51%), totalling 4171 cases. Common procedures included wound management (51%), external fixation (26%), and lower limb amputation (15%). There was prevalence of emergency over elective surgery, performed in rudimentary, secret field hospitals by practitioners lacking formal specialist training or aid-workers. Inadequate documentation and incomplete data capture, due to the conflict, hindered the availability of high-quality, comprehensive surgical datasets within Syria. The focus on emergency surgery is a natural consequence of the prioritisation required with conflict-related pathology, however poor resource availability resulted in challenges in providing basic surgical care. Further research is needed to address gaps in evidence regarding the current state of surgery, training needs, and the quality of care provided.